2003
DOI: 10.1046/j.0004-8461.2003.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated central canal rupture of spinal dermoid: Report of two cases

Abstract: We report two cases of lumbar spinal dermoid cysts with asymptomatic rupture and migration of free fat droplets into the central canal. No fatty droplets were seen within the lumbar subarachnoid space. The presence of fat droplets within the central canal is unusual because the central canal is rudimentary in adults. We suggest that hydromyelia secondary to tumour and specific tumour morphology might facilitate the selective rupture of dermoids into the central canal. We recommend a follow up of these patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Scearce et al 14) reported that fat droplets reach the ventricles from the perimedullary subarachnoid space via retrograde flow through the foramina of Luschka and Magendie. To the best of our knowledge, few cases of ruptureed mature teratoma have been reported 2,5,6,8,14) . In our case, the mature teratoma appeared to have ruptured spontaneously with the intracranial dissemination of fatty droplets.…”
Section: Discussionmentioning
confidence: 99%
“…Scearce et al 14) reported that fat droplets reach the ventricles from the perimedullary subarachnoid space via retrograde flow through the foramina of Luschka and Magendie. To the best of our knowledge, few cases of ruptureed mature teratoma have been reported 2,5,6,8,14) . In our case, the mature teratoma appeared to have ruptured spontaneously with the intracranial dissemination of fatty droplets.…”
Section: Discussionmentioning
confidence: 99%
“…These cases may present with hydrocephalus, meningitis, spinal arachnoiditis or be asymptomatic 3,5 . The rupture can be spontaneously, posttraumatic or postoperatively 3,5 . It is possible that, in the case presented, the large extramedullary tumor of the cauda equine might have ruptured and implanted at the conus medullaris.…”
Section: Fig 3 Histological Analysis Of the Specimens [A] Abundant mentioning
confidence: 99%
“…The patient had no history of spinal manipulation or trauma and any sign of dysraphism on physical and image exams. Its known that spinal dermoid cysts can rupture, and their content can spread throughout the subarachnoid space and ventricular system 3,5 . These cases may present with hydrocephalus, meningitis, spinal arachnoiditis or be asymptomatic 3,5 .…”
Section: Fig 3 Histological Analysis Of the Specimens [A] Abundant mentioning
confidence: 99%
See 2 more Smart Citations